A case of quadriparesis due to renal tubular acidosis accompanied by vitamin D deficiency in Sjögren’s syndrome - Hüzmeli, Can; Candan, Ferhan; Tuncer, Ersin; Timuçin, Meryem; Kayataş, Mansur (International Journal of Research in Medical Sciences, 2017)
Renal tubular acidosis (RTA) is metabolic acidosis disorder with a normal anion gap that occurs resulting from bicarbonate reabsorption or disorder in the hydrogen excretion from the kidney. A variety of tests are required to be administered in a stepwise fashion for the diagnosis and characterization of RTA. Correct diagnosis involves careful evaluation, including exclusion of other entities causing acidosis. The patients were treated with potassium and bicarbonate supplementation. A fifty-one years old female patient presented to the emergency department with quadriparesis dependent on hypokalemia and vitamin D deficiency, was diagnosed with distal renal tubular acidosis (dRTA) combined with Sjögren’s Syndrome (SS). We submitted this case in order to draw attention to the presentation of the RTA with SS.